The influence of single layer MoS2 flake on the propagated surface plasmons of silver nanowire. (18th January 2022) - Lu, Liu; Zhao, Tiantian; Chen, Lei; Wang, Chenyang; Zhou, Zhiqiang; Ren, Xifeng
Abstract: We demonstrate enhancing the excitation and transmission efficiency of the propagated surface plasmon (SP) of an Ag nanowire (Ag NW) in hybrid Ag–MoS2 structures by contrasting the SP propagation of the Ag NW on different substrates, including SiO2 and monolayer MoS2, or partially overlapping the Ag NW on MoS2 flakes. The simulation results show that the leaky radiation of the hybrid plasmonic modes H1 and H2 can be prominently suppressed due to the high refractive index dielectric layer of MoS2, which provides an optical barrier for blocking the leaky radiation, resulting in reduced propagation loss. This paper provides a feasible and effective method to improve the SP propagation length.